HOW THE LOCAL MARKET OPENNESS POLICY TOWARDS FOREIGN WORKERS EFFECTS TURNOVER INTENTION, AND JOB SATISFACTION: A SAUDI ARABIAN PRIVATE SECTOR CONTEXT - Abdulwahab, Mohammed; Alwaheeb, N.; Jianqiao, Liao (European Scientific Journal, ESJ, 2015)
The Saudi Arabian private sector has increasingly shown openness towards foreigners by providing them with a larger fraction of opportunities than the nationals. The increase in the number of foreigners working in the private sector has led to significant change in the local market with much effect on the cost of labor and hiring trends. The tendency has resulted in unrest among the Saudis as they face higher unemployment rates as well as lack of security in the current positions. The entry of more academically qualified foreigners into the market worsens the level of job insecurity as more individuals lack satisfaction in their positions or intend to go for government positions. The current study will examine the effect of local policy openness to foreigners on the turnover intention and job satisfaction with reference to the Saudi Arabia private sector context. The lack of job security will mediate the effect of the local market policy openness to foreigners on the turnover intention and job satisfaction. On the other hand, the level of education will moderate the relationship between the local market openness to foreigners and the job security while the organizational justice will moderate the effect of job security on satisfaction and the turnover intention.